Improving iron status before pregnancy predictors for time to first pregnancy in rural Bangladesh - Khambalia, Amina; Choudhury, Nuzhat; Zlotkin, Stanley (BRAC Research and Evaluation Division (RED), 2019)
It has recently been advocated that iron supplementation begin before childbearing. A key operational issue is timely identification of !~males prior to pregnancy. The purpose of this study was to examine factors associated with time to first pregnancy ( FP) and adolescent pregnancy (AP). /\ cross-sectional survey was conducted in Gazipur. Bangladesh (April-May 2006) among ever married females aged < 50 y. Data on 603 females were analysed. Mean age was 32 y .t 9. Only 15%, (7/47) of never pregnant females reported iron use in the past 6 mo. Mean age at marriage was 17 y 1: 3 at marriage. 58% (322/556) of females were < l8 y at fP. Median time from marriage to FP was 12 mo (range: 0-408). Multivariate hazard analysis found risk of pregnancy increased by 13% for every y increase in age at marriage ( p<O.OOO I) and decreased by 3% for every y increase in female's current age (p·~O.OOO I). Risk among medical contraceptive users was 58% of the risk among non-users (p'-='0.000 I). Using multivariate logistic regression analysis the probability of an AP decreased by 3% for each y of marriage during adolescence (CI: 0.95-0.99), by 10% for every y increase in husband's age at marriage (CI: 0.87-0.94), by 68% among female wage earners compared to non-wage earners (CI: 0.16-0.64) and by SO% among medical contraceptive users compared to non-users (CI: 0.30-0.85). In this population females arc married at a young age with short time to FP intervals. Pcriconceptional iron supplementation programs should target adolescents and newly-weds.